Tampilan kualitas susu sapi perah akibat imbangan konsentrat dan hijauan yang berbeda (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The aim of this study was to assess the optimal balance ration of concentrate and forage to improve dairy milk production. The research was conducted at regional operational unit Mulyorejo, Barukan village, Tengaran Sub District, Semarang Regency, and Banyu Aji Cooperative, Getasan Sub District, Semarang Regency. Data was analyzed at Feed Nutrition Science Laboratory, Faculty of Animal Husbandry and Agriculture, Diponegoro University Semarang. The research started from June 29 to July 31, 2014. The materials of this research were 12 Friesian Holstein dairy cows in second and third months of lactation with average estimated body weight 408.5±30.86 kg (Coefficient of Variance (CV) = 10.68%) with average milk production around 9.3±1.01 liters (CV = 14.33%). The study was experimental research with completely randomized design using three treatments, i.e. T0 (50% of concentrate and 50% of forage), T1 (45% of concentrate and 55% of forage) and T2 (40% of concentrate and 60% of forage). The results showed that T2 had a significant effect on milk fat content (P<0.05), solid non fat (SNF) content (P<0.05), milk protein content (P<0.01) and milk lactose content (P<0.05). This study concluded that the optimal balance ration of concentrate and forage to improve milk performance consisted of 40% of concentrate and 60% of forage. Keywords: Dairy cow, NDF, milk fat, solid non fat